Poor Postnatal Weight Growth is a Late Finding After Sepsis in Very Preterm Infants - Flannery, Dustin D. (Arch Dis Child Fetal Neonatal Ed, 2020)
OBJECTIVE: To characterize the association between sepsis and postnatal weight growth when accounting for the degree of growth restriction present at birth. DESIGN: Retrospective matched cohort study using data from the Postnatal Growth and Retinopathy of Prematurity study. Participants were born with birth weights <1500g or gestational ages <32 weeks between 2006–2011 at 29 neonatal centers in the US and Canada. Sepsis was defined as a culture-confirmed blood, cerebrospinal fluid bacterial or fungal infection before 36 weeks’ postmenstrual age. Growth was assessed as the change in weight z-score between birth and 36 weeks’ postmenstrual age. RESULTS: Of 4,785 eligible infants, 813 (17%) developed sepsis and 693 (85%) were matched 1:1 to controls. Sepsis was associated with a greater decline in weight z-score (mean difference −0.09, 95% CI [−0.14, −0.03]). Postnatal weight growth failure (decline in weight z-score >1) was present in 237 (34%) infants with sepsis and 179 (26%) controls (adjusted odds ratio 1.49, 95% CI [1.12, 1.97]). Longitudinal growth trajectories showed similar initial changes in weight z-scores between infants with and without sepsis. By three weeks after sepsis onset, there was a greater decline in weight z-scores relative to birth values in those with sepsis than without sepsis (delta z-score −0.89 vs −0.77; mean difference −0.12, 95% CI −0.18, −0.05). This significant difference persisted until 36 weeks’ or discharge. CONCLUSION: Infants with sepsis had similar early weight growth trajectories as infants without sepsis, but developed significant deficits in weight that were not apparent until several weeks after the onset of sepsis.